2016
DOI: 10.1016/j.neuroimage.2015.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Imaging fast electrical activity in the brain with electrical impedance tomography

Abstract: Imaging of neuronal depolarization in the brain is a major goal in neuroscience, but no technique currently exists that could image neural activity over milliseconds throughout the whole brain. Electrical impedance tomography (EIT) is an emerging medical imaging technique which can produce tomographic images of impedance changes with non-invasive surface electrodes. We report EIT imaging of impedance changes in rat somatosensory cerebral cortex with a resolution of 2 ms and < 200 μm during evoked potentials us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 52 publications
7
106
0
1
Order By: Relevance
“…When considering the localisation accuracy alone, the results obtained here are not dissimilar from those presented previously by Aristovich et al (2016). They simulated a conductivity change of 1% and considered only additive noise of 0.5 μV and were able to attain a localisation accuracy of less than 1 mm throughout the brain.…”
Section: How Deep Does Modelling Suggest We Can Image Activity?supporting
confidence: 55%
See 2 more Smart Citations
“…When considering the localisation accuracy alone, the results obtained here are not dissimilar from those presented previously by Aristovich et al (2016). They simulated a conductivity change of 1% and considered only additive noise of 0.5 μV and were able to attain a localisation accuracy of less than 1 mm throughout the brain.…”
Section: How Deep Does Modelling Suggest We Can Image Activity?supporting
confidence: 55%
“…Previous measurements of cortical impedance changes during evoked activity in the cortex include those undertaken by Aristovich et al (2016) and Oh et al (2011); they reported maximum amplitudes of 0.007% and 0.1% respectively. In the current work the cortical impedance change had a larger mean amplitude of À0.16 AE 0.08%.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litermentioning
confidence: 99%
See 1 more Smart Citation
“…Until now EIS has had an extensive application in biological research. According to the biological objects, application of EIS can be divided into three aspects, that is, electrical impedance tomography in medical imaging [2][3][4], quality and safety assessment in food industry, and phytophysiology in agronomy [5][6][7]. Research objects and targets of EIS applied in food are abundant and extensive, including for fruits, such as study on dry matter content of durian [8] and ripening of banana [9], for vegetables, such as changes in potato and spinach tissues during or after heating [10,11] and moisture content of carrot slices during drying [12], for meat, such as quality evaluation of pork meat during storage [13] and investigation of beef meat behavior during ageing [14], for chicken, such as discrimination of fresh and frozen-thawed chicken breast muscles [15], for fish, such as salt and moisture content determination of salted rainbow trout [16] and freshness estimation of carp [17], for dairy products, such as real-time detection of bovine milk adulteration [18], and moreover for determination of the additives content in natural juices [19], fermentation process of bread dough [20], and quality assessment of cooking oil [21].…”
Section: Introductionmentioning
confidence: 99%
“…MREIT, which is sensitive to conductivity contrast (a scalar), involves administration of external currents to probe conductivity properties. In the case of neural activity, MREIT may be able to detect changes in membrane conductance associated with neural spiking (functional MREIT, fMREIT) in a similar manner to the related technique of fast neural electrical impedance tomography (Aristovich et al 2016, Vongerichten et al 2016). While the contrast mechanisms of fMREIT and fast neural EIT are the same, fMREIT has the advantage that signals from deep cortical structures can potentially be recovered, and implanted electrodes need not be used.…”
Section: Introductionmentioning
confidence: 99%